Estimation of Threshold Level of Interest Rate and Analysis of Determinants of GDP For Pakistan - Nimra Shoukat; Dr. Naseer Shahzada (Dialogue Social Science Review (DSSR), 2025)
This study aims to calculate the threshold level of interest rate for Gross Domestic Product (GDP), moreover this study also intended to explore the major determinants of the GDP which are inflation, money supply, interest rate, and investment. Very few studies in Pakistan have estimated the threshold level of interest rate for GDP in Pakistan so this the research gap for this study. This study employed time series data starting from 1991- 2024. The study employed the Augmented Dickey Fuller Test, Non-linear Threshold model and Autoregressive Distributive Lag model for the analysis of the data. Results from the non-linear regression model found the threshold level interest rate of 11% is the threshold level of interest for Pakistan. Which means that up to 11 % the interest rate will have a positive impact on the GDP while after 11 % interest rate has inverse impact on the GDP. Results from the ARDL model revealed positive long run effect of inflation, money supply, and investment on GDP, while interest rate has a negatively affect to GDP. This study recommends that we gradually bring down the interest rate at 9-10 % because a 9% interest rate is beneficial for the economy. Increase money supply that reduce interest rate which increase investment and consumption expenditure thereby increasing national income and employment.